MAQASHID SYARIAH SEBAGAI FRAMEWORK MANAJEMEN PENDIDIKAN ISLAM DI ERA DISRUPSI DIGITAL - Ahmad Muqaffi; Bahrani; Sudadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The era of digital disruption has brought fundamental changes to the management of Islamic educational institutions. Globalization, digitalization, and Artificial Intelligence (AI) present both opportunities and serious threats to the fundamental Islamic values embedded in educational practice. This article examines Maqashid Sharia as a strategic framework for Islamic education management in responding to the challenges of the digital disruption era. Using a qualitative library research method, this article analyzes the five dimensions of Maqashid Sharia — hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, and hifz al-mal — as normative and operational foundations for comprehensive Islamic educational resource management. The findings indicate that the Maqashid Sharia framework provides holistic guidance in formulating digital-based curriculum policies, developing educator competencies in the AI era, adaptive institutional governance, and protecting Islamic identity and values amid globalization. This article proposes a three-level implementation model — macro, meso, micro — as practical guidance for Islamic educational institution managers in conducting digital transformation rooted in Islamic principles.